COX‐2 inhibitors arrest prostate cancer cell cycle progression by down‐regulation of kinetochore/centromere proteins. Issue 10 (7th May 2014) - Bieniek, Jared; Childress, Chandra; Swatski, Matthew D.; Yang, Wannian
<x xml:space="preserve">Abstract</x> BACKGROUND Previous studies have shown that COX‐2 inhibitors inhibit cancer cell proliferation. However, the molecular mechanism remains elusive. METHODS Prostate cancer LNCaP, 22Rv1, and PC3 cells were cultured and treated with the COX‐2 inhibitors celecoxib and CAY10404. Knockdown of COX‐2 in LNCaP cells was carried out using lentiviral vector‐loaded COX‐2 shRNA. Cell cycle progression and cell proliferation were analyzed by flow cytometry, microscopy, cell counting, and the MTT assay. The antagonists of EP1, EP2, EP3, and EP4 were used to examine the effects of the PGE2 signaling. The effect of COX‐2 inhibitors and COX‐2 knockdown on expression of the kinetochore/centromere genes and proteins was determined by RT‐PCR and immunoblotting. RESULTS Treatment with the COX‐2 inhibitors celecoxib and CAY10404 or knockdown of COX‐2 significantly inhibited prostate cancer cell proliferation. Flow‐cytometric analysis and immunofluorescent staining confirmed the cell cycle arrested at the G2/M phase. Biochemical analysis showed that inhibition of COX‐2 or suppression of COX‐2 expression induced a dramatic down‐regulation of key proteins in the kinetochore/centromere assembly, such as ZWINT, Cdc20, Ndc80, CENP‐A, Bub1, and Plk1. Furthermore, the EP1 receptor antagonist SC51322, but not the EP2, EP3, and EP4 receptor antagonists, produced similar effects to the COX‐2 inhibitors on cell proliferation and down‐regulation of kinetochore/centromere proteins, suggesting that the effect of the COX‐2 inhibition is through inactivation of the EP1 receptor signaling. CONCLUSIONS Our studies indicate that inhibition of COX‐2 can arrest prostate cancer cell cycle progression through inactivation of the EP1 receptor signaling and down‐regulation of kinetochore/centromere proteins. Prostate 74:999–1011, 2014. © 2014 Wiley Periodicals, Inc.